International standards to document remaining autonomic function after spinal cord injury - Krassioukov, Andrei (Maney Publishing, 2012)
This is the first guideline describing the International Standards to document remaining Autonomic Function after Spinal Cord Injury (ISAFSCI). This guideline should be used as an adjunct to the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) including the ASIA Impairment Scale (AIS), which documents the neurological examination of individuals with SCI. The Autonomic Standards Assessment Form is recommended to be completed during the evaluation of individuals with SCI, but is not a part of the ISNCSCI. A web-based training course (Autonomic Standards Training E Program (ASTeP)) is available to assist clinicians with understanding autonomic dysfunctions following SCI and with completion of the Autonomic Standards Assessment Form (www.ASIAlearningcenter.com).